APPLYING THE NEW LEX MERCATORIA BY OPTING-OUT APPROACH IN SETTLEMENT OF INTERNATIONAL COMMERCIAL CONTRACT DISPUTES - Taufiqurrahman, Taufiqurrahman (Department of Transnational Business Law, Faculty of Law Universitas Padjadjaran, 2020)
The problem that must be solved at first in international commercial contract dispute settlement is the determination of applicable law. This problem is not easy to be solved in the absence of a choice of law clause. Generally, judges or arbitrators attempt to use conventional methods of determination that ultimately designate national law from either party. This conventional method certainly creates a sense of injustice for one of the parties whose national law is not embarrassed. From the condition above, the existence of an international law regime (the New Lex Mercatoria made by International Organizations operating in the field of International Commercial Law) as well as an approach that enforces the law regime is urgently needed in international trade traffic. The purpose of this study was to determine the importance of using an opting-out approach to enforce the New Lex Mercatoria in the resolution of commercial disputes encountered. The research method used is normative legal research method with the statute and conceptual approach. The results show that the